Challenges to Education Policy in Rwanda: A review into preschool education - Nadege, Muhimpundu; Annonciata, Akimanizanye (Advances in Social Sciences Research Journal, 2021)
Although ,Rwanda has approved its Early Childhood Development (ECD) Policy and Strategic Plan in September 2011, the policy was established and implemented in different ways in early childhood education, yet preschool has a long way to go. Equally, having a focus on preschool education is the best investment that Rwanda can make to achieve other national goals such as, reducing maternal mortality, eliminating malnutrition and improving access to quality education. Empirical evidence gathered from secondary sources indicates that government has put more effort in improving quality of education. Yet on preschool level, indicators available illustrates that the results are far from expectation. The study further discusses the challenges faced by government in the design and implementation of ECD policy that have led to the ensuing situation.